African Forensic Sciences Academy (AFSA): An emerging movement in Africa (Forensic science international, 2025)
Forensic science bodies their respective regions and form the foundation for best practice. Until recently, no officially registered body existed that represented all forensic science practitioners across Africa. The African Forensic Sciences Academy (AFSA) was founded in December 2022 for this reason to serve African forensic science practitioners. This article details the progress of AFSA to date, highlights its core values and mission, and outlines the way forward for this newly established Academy. •Diversity of practice, frameworks and structures in Africa called for a representative body for all forensic scientists.•AFSA is the first formally registered body with independent oversight in Africa for forensic science.•AFSA promotes excellence and integrity in forensic science in Africa.